Characteristic time scales of evaporation from a subarctic reservoir. Issue 3 (9th March 2023) - Pierre, Adrien; Nadeau, Daniel F.; Thiboult, Antoine; Rousseau, Alain N.; Tremblay, Alain; Isabelle, Pierre‐Erik; Anctil, François
Abstract: Water bodies such as lakes and reservoirs affect the regional climate by acting as heat sinks and sources through the evaporation of substantial quantities of water over several months of the year. Unfortunately, energy exchange observations between deep reservoirs and the atmosphere remain rare in northeastern North America, which has one of the highest densities of water bodies in the world. This study characterizes the dynamics of turbulent heat fluxes by analysing in‐situ observations of a compact and dimictic reservoir (50.69° N, 63.24° W) located in a subarctic environment. The reservoir is characterized by a mean depth of 44 m and a surface area of 85 km 2 . Two eddy covariance (EC) systems, one on a raft and one onshore, were deployed from 27 June 2018 to 12 June 2022. The thermal regime of the reservoir was monitored using two vertical chains of thermistors. Results indicate a mean annual evaporation rate of 590 ± 66 mm, which is equivalent to ≈51% of the annual precipitation, with 84% of the evaporation occurring at a high rate from August to freeze‐up in late December through episodic pulses. It was difficult to close the energy balance because of the magnitude and the large time lag of the heat storage term. To circumvent this problem, we opted to perform calculations for a year that started from the first of March, as the heat storage in the water column was at its lowest at that point and could thus be ignored. From June to December, monthly Bowen ratios increased from near‐zero negative values to about 1.5. After September, due to smaller vapour pressure deficits, latent heat fluxes steadily decreased until the reservoir had a complete ice cover. Opposite diurnal cycles of sensible and latent heat fluxes were revealed during the open water period, with sensible heat fluxes peaking at night and latent heat fluxes peaking in the afternoon. Abstract : The annual evaporation from a subarctic reservoir was measured at 442 mm on average based on a 4‐year eddy‐covariance measurement campaign. This value was adjusted to 590 mm following the assessment of the associated energy balance, which revealed an underestimation of about 26% of the turbulent fluxes. More precisely, 84% of the total annual evaporation took place from August to December only when the atmosphere was mostly unstable. Moreover, the sensible heat flux was negative from January to July and peaked in December by 50% higher than the latent heat flux. Finally, evaporation was mainly controlled by wind speed and air humidity, whereas it did not seem to be affected by the duration of reservoir freeze‐up.